Pyrazole Substituted 9-Anilinoacridines as HER2 Inhibitors Targeting Breast Cancer - An in-silico approach - Rajagopal, Kalirajan; Sri, Vulsi B.; Byran, Gowramma; Gomathi, Swaminathan (Current Drug Research Reviews, 2022)
Background: Breast cancer is one of the malignant tumours which mainly affect the female population. 20% of the cases of breast cancer are due to the over-expression of Human epidermal growth factor receptor-2 (HER2), which is the dominant tyrosine kinase receptor. In general, 9-anilinoacridine derivatives play an important role in antitumor activity due to their DNA-intercalating properties. Objective: Some novel 9-anilinoacridines substituted with pyrazole moiety (1a-z) were designed and their HER2enzyme (PDB id-3PP0) inhibition activity was performed by molecular docking studies using the Glide module of Schrodinger suite 2019-4. Methods: Glide module of the Schrodinger suite was used to perform docking studies; qikprop module was used for in-silico ADMET screening and the Prime-MMGBSA module was used for free binding energy calculations. Based on GLIDE scoring functions, we can determine the binding affinity of ligands (1a-z) towards HER2. Results: The inhibitory activity of ligands against HER2 was mainly due to the strong hydrophobic and hydrogen bonding interactions. Almost all the compounds 1a-z exhibited a good binding affinity with Glide scores in the range of -4.9 to -9.75, when compared with the standard drugs CK0403 (-4.105) and Tamoxifen (-3.78). From the results of in-silico ADMET properties, it was evident that most of the compounds fell within the recommended values. MM-GBSA binding calculations of the most potent inhibitors were found to be more favourable. Conclusion: The results of in-silico studies provide strong evidence for the potential of valuable ligands in pyrazole substituted 9-anilinoacridines as HER2 inhibitors, and the compounds, 1v,s,r,d,a,o with significant Glide scores may produce significant anti-breast cancer activity.
Keywords: in-silico ADMET screening